Dietary habits, depression and obesity: an intricate relationship to explore in pediatric preventive strategies - Calcaterra, Valeria; Rossi, Virginia; Magenes, Vittoria Carlotta; Baldassarre, Paola; Grazi, Roberta; Loiodice, Martina; Fabiano, Valentina; Zuccotti, Gianvincenzo (Frontiers in Pediatrics, 2024)
Obesity and depression represent major health problems due to their high prevalence and morbidity rates.Numerous evidences elucidated the connections between dietary habits and the incidence or severity of depression. This overview aims to investigate the intricate relationship between dietary patterns and depression with the objective of elaborating preventive strategies for childhood obesity. Literature data recognized that there is a link between mood and food choices, with certain foods selected for their impact on the brain's reward centers. This behavior parallels the one observed in substance addiction, suggesting a specific neural mechanism for food addiction that contributes to overeating and obesity. It is important to note the significant correlation between obesity and depression, indicating a shared biological pathway influencing these conditions. Stress substantially affects also eating behaviors, often leading to increased consumption of pleasurable and rewarding foods. This can trigger a cycle of overeating, weight gain, and psychological distress, exacerbating mood disorders and obesity. In addition, consumption of certain types of foods, especially "comfort foods" high in fat and calories, may provide temporary relief from symptoms of depression, but can lead to long-term obesity and further mental health problems. Understanding these complex interactions is critical to developing preventive strategies focusing on dietary, emotional, and environmental factors, thereby reducing the risk of obesity and mood disorders.